К юбилею Нины Дмитриевны Еропкиной - Шарыгин, Михаил Дмитриевич; Лучников, Андрей Сергеевич; Сероваева, Е. К.; Чекменева, Лариса Юрьевна (Географический вестник=Geographical bulletin, 2017)
doi 10.17072/2079-7877-2015-4-103-111